2007
DOI: 10.1111/j.1460-9568.2006.05274.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency stimulation of the direct cortical input to area CA1 induces homosynaptic LTD and heterosynaptic LTP in the rat hippocampal–entorhinal cortex slice preparation

Abstract: The entorhinal cortex (EC) innervates area CA1 and the subiculum directly via the portion of the perforant path, which originates from EC layer III cells referred to as direct cortical input (dCI), and indirectly via the trisynaptic loop through the dentate gyrus and area CA3. The dCI is of great importance as it mediates positional information for activation of place cells that is not prevented after interrupting information flow from area CA3 to CA1. In this study, we investigated the effects of low-frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
2
30
0
1
Order By: Relevance
“…In addition to modulating phasic responses in a context-dependent manner, changes in background firing rate during operant sessions may also contribute to certain forms of context-dependent learning. The long-lasting changes in background firing rates of single neurons are similar to firing rates produced by sustained low-frequency stimulation parameters that have been used to induce certain forms of synaptic depression and potentiation (Dudek and Bear, 1992;Froc and Racine, 2005;Huang and Kandel, 2005;Wohrl et al, 2007). Similar activity-dependent adaptations may occur in vivo as a result of sustained changes in background firing rate like those observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…In addition to modulating phasic responses in a context-dependent manner, changes in background firing rate during operant sessions may also contribute to certain forms of context-dependent learning. The long-lasting changes in background firing rates of single neurons are similar to firing rates produced by sustained low-frequency stimulation parameters that have been used to induce certain forms of synaptic depression and potentiation (Dudek and Bear, 1992;Froc and Racine, 2005;Huang and Kandel, 2005;Wohrl et al, 2007). Similar activity-dependent adaptations may occur in vivo as a result of sustained changes in background firing rate like those observed in this study.…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies have suggested that kainate receptors participated in the short-and long-term synaptic plasticity of both excitatory and inhibitory transmission (Christensen et al, 2004;Lauri et al, 2006). The homosynaptic long-term depression induced by low-frequency stimulation of the direct cortical input to CA1 area depended on the activation of kainate receptors (Wöhrl et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Heterosynaptic disinhibition mediated by temporoammonic inputs has been observed in the CA1 region as well (Wohrl et al, 2007). In that study, homosynaptic LTD was GABA B and kainate receptor-dependent, whereas heterosynaptic potentiation was mediated by GABA A and metabotropic glutamate receptors.…”
Section: Discussionmentioning
confidence: 96%
“…In various systems, synaptic plasticity at GABAergic synapses contributes to the regulation of overall excitability and somatic output (Gaiarsa et al, 2002;Mody, 2005). Synaptic plasticity at hippocampal output synapses seems to be modulated by local inhibition that is controlled by the deep layers of the EC (Behr et al, 1998;Wohrl et al, 2007). Accordingly, the Sub might function as an integrator of sensory information transformed by the trisynaptic circuit with positional signals conveyed by the temporoammonic pathway (Naber et al, 2000;Brun et al, 2008).…”
Section: Discussionmentioning
confidence: 97%